Inconsistencies of Political Movements in Nepal: An Overview - Gautam, Dilli Raj (Interdisciplinary Issues in Education, 2024)
Using qualitative, analytical, and historical research methodology, this article examines the inconsistencies of the political movements that occurred in Nepal for the institutionalization of a democratic system of governance. For many years, the political movement for social change in Nepal has struggled against the immediate government's authoritarian rule. The majority of people have organized together and revolted over time for the attainment of democracy, freedom, equality, and the rule of law in addition to human rights. There have been several turmoil observed between the social revolution and the political movement. It scrutinizes the origin, nature, dynamics, and mobilization of political movements as it was targeted to transform prevailing dominant social, economic, and political disorder. Every political shift ought to be in the best interests of millions of people. The study has extensively been more historical, descriptive and analytical. This paper suggests ways to solve the expectations of the people awaken after the political transformation in different stages with the critical study and analysis of historical and legal primary and secondary sources manifested by the political forces pre and post-political transitoriness.